2019
DOI: 10.1001/jamaneurol.2018.3077
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Gabapentin vs Pregabalin on Pain Intensity in Adults With Chronic Sciatica

Abstract: IMPORTANCEOptimal pharmacologic treatment for chronic sciatica (CS) is currently unclear. While gabapentin (GBP) and pregabalin (PGB) are both used to treat CS, equipoise exists. Nevertheless, pharmaceutical regulation authorities typically subsidize one drug over the other. This hinders interchange wherever the favored drug is either ineffective or ill-tolerated.OBJECTIVE To assess GBP vs PGB head to head for the treatment of CS. DESIGN, SETTING, AND PARTICIPANTSA preplanned interim analysis of a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 11 publications
(29 reference statements)
2
38
1
6
Order By: Relevance
“…Recently, several clinical trials have suggested the efficacy of GABA use for off-label pain conditions (e.g. chronic sciatica; irritable bowel syndrome) and for reducing acute and chronic postoperative pain and OPI use [50][51][52][53][54][55]. However, given the safety concerns about GABAs, there have been calls for placing more stringent regulations on gabapentin at the federal level and to include gabapentin monitoring in state prescription drug monitoring programs (PDMPs) to promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinical trials have suggested the efficacy of GABA use for off-label pain conditions (e.g. chronic sciatica; irritable bowel syndrome) and for reducing acute and chronic postoperative pain and OPI use [50][51][52][53][54][55]. However, given the safety concerns about GABAs, there have been calls for placing more stringent regulations on gabapentin at the federal level and to include gabapentin monitoring in state prescription drug monitoring programs (PDMPs) to promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…The effect size of pregabalin and its clinical usefulness are currently sources of debate [ 46 , 47 ]. Recent recommendations issued by the French chapter of the IASP and the French Society of Neurology [ 46 ] have proposed pregabalin as an alternative to gabapentin for second-line treatment, given that different studies [ 3 , 48 ] have shown that gabapentin has a relatively large effect size and tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been concerns about misuse, diversion, and dependence with long-term use of these medications. These medications may have a theoretical role in patients whose LBP has a strong neuropathic component [24], but the number needed to treat is high. A medication trial period of up to 4 weeks at therapeutic doses followed by cessation in absence of benefit is reasonable.…”
Section: Gabapentinoidsmentioning
confidence: 99%